Evaluasi Manajemen dan Tatakelola Teknologi Informasi pada Dinas Kominfo Kota Malang dengan menggunakan Framework Cobit 2019 - Achmad Muchsinul Huda Malik Jamil; Aditya Rachmadi; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Department of Communication and Information Technology of Malang City is a government organization that is engaged in data and information processing for the public or other government agencies, which has implemented the use of IT in its processes. So that they have to carry out IT management/management activities, which after the interview arose the problem of how the current management is preparing to deal with IT developments. Starting from prioritizing which IT management/governance processes should be prepared first. COBIT 2019 has a Design Factor process that main purposes is to find out which processes are crucial for the organization (along with the target level) to focus on. The researcher saw that the Design Factor process was in accordance with the problem at the Department. Then the Design Factor process was carried out to the department with the final result of the focus process being BAI11 with a target of level 3. Then it was evaluated according to COBIT 2019 and the level of BAI11 was 2 (gap of 1 from the target). Then the formulation of recommendations to bridge the gap is carried out with the final result of 4 recommendations.